Age differences in central and peripheral intraocular pressure using a rebound tonometer. Issue 12 (2nd August 2006) - González-Méijome, J M; Jorge, J; Queirós, A; Fernandes, P; Montés-Micó, R; Almeida, J B; Parafita, M A
Abstract : Aim: To evaluate the influence of age on the measurements and relationships among central and peripheral intraocular pressure (IOP) readings taken with a rebound tonometer. Methods: The IOPs were measured using the ICare rebound tonometer on the right eyes of 217 patients (88 men and 129 women) aged 18–85 years (mean 45.9 (SD 19.8) years), at the centre and at 2 mm from the nasal and temporal limbus along the horizontal meridian. Three age groups were established: young (⩽30 years old; n = 75), middle aged (31–60 years old; n = 77) and old patients (>60 years old; n = 65). Results: A high correlation was found between the central and peripheral IOP readings, with the central readings being higher than the peripheral ones. Higher IOP values for the central location were found in the younger patients. Older patients had significantly lower temporal IOP readings than those for the remaining two groups (p<0.001), whereas no significant differences were found among groups when IOP was measured at the central and nasal locations. A significant decrease was observed in the nasal and temporal IOP readings as the age increased (p = 0.011 and 0.006, respectively). Conclusion: Older patients had lower IOP values than the middle-aged and younger patients in the temporal peripheral location. A negative correlation was found between age and IOP by rebound tonometry in the corneal periphery but not in its centre.